PROLEGOMENA OF INFORMATION REALITY: SCRIPT, TEXT, KNOWLEDGE, EDUCATION - Машталер, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article discusses the genesis of information reality, which is going through a formation from the preliterate to the Internet and examines the phenomena of conditioning knowledge of humanity, education, culture of thinking.